How to put into practice the Integration Methods - Umarova Shirinoy Sadilloyevna (Universitas Muhammadiyah Sidoarjo, 2019)
Till graduating bachelor's degree at University it is admittable fact that most graduators essentially practice only on receiving specific knowledge, resulted that the lack of Utilisation of educational intelligence that is way it is purposed to lead the fresh bachelors of pedagogical units of High Education getting on how to deliver their learners obtained substances. It is directed that analyzing of Integration that promotable comprehensive Methodology on Teaching English language. Furthermore, the strategies of the integrating skills and the techniques about how to present knowledge during the procedure of lesson at GES (general education schools). It is brilliant brief instruction not only for the new teachers who just starting working with learners but also for the experienced teachers.